A facile and efficient method for synthesis of macrocyclic lipoglycopeptide. Issue 7 (18th February 2015) - Zhao, Qingjie; Li, Xiang; Li, Wenjuan; Zou, Yan; Hu, Honggang; Wu, Qiuye
Abstract: An efficient and practical method for macrocyclic lipoglycopeptide synthesis was developed and utilized to synthesize lipoglycosylated derivatives of Tyrocidine A. The method is based on solid-phase peptide synthesis using 2-chlorotrityl resin as the solid-phase support and lipoglycosyl amino acids as building blocks. This synthetic method should be generally applicable to various macrocyclic lipoglycopeptides. Graphical abstract: